The effectiveness of moral disengagement and social norms as anti‐bullying components: A randomized controlled trial. Issue 6 (25th July 2022) - Tolmatcheff, Chloé; Galand, Benoit; Roskam, Isabelle; Veenstra, René
Abstract: This three‐armed randomized controlled trial examined how moral disengagement and social norms account for change in bullying behavior and their potential as targets of anti‐bullying components within separate interventions among 1200 French‐speaking Belgian elementary students (48% boys, 9–12 year‐olds, 57 classes, nine schools) during 2018–2019 (no ethnicity data available). Mediation analysis revealed that students' moral disengagement successfully decreased ( β  = −.46), which, in turn, reduced both bullying ( β  = .33) and outsider behaviors ( β  = .20), and increased defending ( β  = −.10). Intervening on social norms decreased bullying ( β  = −.18), but not through the perceived injunctive class norm as intended. Guidelines to open the "black box" of anti‐bullying programs and determine the cost‐effectiveness ratio of their components are provided.